An evaluation of the periodical collection and its use in the Lung Center of the Philippines Medical Library - Torres, Ma. Crineza B. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
The medical library assumes increasing importance in providing quality library and information services to support and enhance the medical hospital. With the fast pacing of technology in the medical field, this study was conducted to determine the periodical collection of the Lung Center of the Philippines medical library and its compliance with the Brandon/Hill selected list of print books and journals for the small medical library.